Impact of Homestays on Socio-economic Opportunities of the Local Community - Woli, Lokendra (KMC Journal, 2022)
Homestays have settled current encouraging tourism becoming an important source of income for many families in rural areas of Nepal. Homestay has supported the local and external visitors to learn about the local culture, custom, traditions, and diversity among others. The objective of this study was to find out the socio-economic opportunities and its impact on local community of Dallagaon, Bardiya. This study further observed the cultural impact of homestays on the host community. Concurrent mixed-methods research design was used to understand the situation of homestay at the destination by using the questionnaire, interview and key informant information as the tools. Data were analyzed by descriptive and inferential statistics. The result shows that homestays plays the vital role to conserve the culture by increasing local product and to empower in the education by increasing the economic conditions. It helps to improve communication skills as well as reduce migration problems and hence supportive for local employment. There is no significant difference between the economic and socio-cultural impact of homestays on the host community as perceived by homestay operators in the sample according to the t-test analysis. Dallagaon may be the best destination for those tourists who seek rich, unique and firsthand Tharu culture. The local communities are becoming more aware of their cultural identity, preservation, and the creation of new local infrastructure. It will contribute the creation of more job opportunities, infrastructure development, and essentially poverty reduction.